Ski acts as a co-repressor with Smad2 and Smad3 to regulate the response to type β transforming growth factor - Xu, Weidong (The National Academy of Sciences, 2000)
The c-ski protooncogene encodes a transcription factor that binds DNA only in association with other proteins. To identify co-binding proteins, we performed a yeast two-hybrid screen. The results of the screen and subsequent co-immunoprecipitation studies identified Smad2 and Smad3, two transcriptional activators that mediate the type β transforming growth factor (TGF-β) response, as Ski-interacting proteins. In Ski-transformed cells, all of the Ski protein was found in Smad3-containing complexes that accumulated in the nucleus in the absence of added TGF-β. DNA binding assays showed that Ski, Smad2, Smad3, and Smad4 form a complex with the Smad/Ski binding element GTCTAGAC (SBE). Ski repressed TGF-β-induced expression of 3TP-Lux, the natural plasminogen activator inhibitor 1 promoter and of reporter genes driven by the SBE and the related CAGA element. In addition, Ski repressed a TGF-β-inducible promoter containing AP-1 (TRE) elements activated by a combination of Smads, Fos, and/or Jun proteins. Ski also repressed synergistic activation of promoters by combinations of Smad proteins but failed to repress in the absence of Smad4. Thus, Ski acts in opposition to TGF-β-induced transcriptional activation by functioning as a Smad-dependent co-repressor. The biological relevance of this transcriptional repression was established by showing that overexpression of Ski abolished TGF-β-mediated growth inhibition in a prostate-derived epithelial cell line.